2021
DOI: 10.31635/ccschem.020.202000515
|View full text |Cite
|
Sign up to set email alerts
|

Improving Water Stability of Metal–Organic Frameworks by a General Surface Hydrophobic Polymerization

Abstract: Water and moisture stability has been recognized as one of the most important concerns of metal-organic frameworks (MOFs) in relation to their future applications. Nonetheless, the majority of MOFs are more or less water-labile. One promising solution for the collapse of MOFs towards water is surface hydrophobic modification. Herein, a facile, mild and general one-step surface polymerization approach has been developed to coat the exterior surface of MOF particles with a thin polymer layer. Remarkably, the hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(71 citation statements)
references
References 23 publications
0
71
0
Order By: Relevance
“…It is noteworthy that both researchers reported that PMDS [47] or PDMS-Cat [48] coating not only boost hydrophobicity of the MOFs, but also retain their catalytic performance in the presence of water molecules.…”
Section: Addition Of Hydrophobic Coatingmentioning
confidence: 99%
See 3 more Smart Citations
“…It is noteworthy that both researchers reported that PMDS [47] or PDMS-Cat [48] coating not only boost hydrophobicity of the MOFs, but also retain their catalytic performance in the presence of water molecules.…”
Section: Addition Of Hydrophobic Coatingmentioning
confidence: 99%
“…MOF-based photocatalytic membrane have also been reported in several other fields of application, such as oil and water separation [158,159], phenol removal [160], and organic pollution [47,161]; which generally show that the MOF addition within the photocatalyst membrane can significantly improve the membrane performance although still challenging to conduct. Summary of MOFs-based MMM's performance is presented in Table 5.…”
Section: Mofs As Photocatalytic Filler For Photocatalytic Membranementioning
confidence: 99%
See 2 more Smart Citations
“…If the typical MOFs hosts can improve the stability of 3 crystal structure in more organic solvents, the detected scope of guest molecules can be further extended. 5,[28][29] In fact, many MOFs are designed with extremely high symmetry, which are suitable for gas adsorption.…”
Section: Introductionmentioning
confidence: 99%